Evaluation and analysis of theoretical knowledge proficiency and practical skills among parasitic disease practitioners in Hainan province: a cross-sectional survey - Wenjuan Liang; Guangda Xu; Xiaomin Huang; Shuming Yang; Rongguang Zhang; Yuchun Li (Frontiers in Public Health)
ObjectiveThis study aimed to evaluate both theoretical knowledge proficiency and practical skills among practitioners specializing in parasitic diseases in Hainan province, providing essential groundwork for ongoing capacity enhancement efforts.MethodsA cross-sectional study using two-stage stratified random sampling was conducted in Hainan province. City or county-level representatives from Centers for Disease Control and Prevention and other institutes, as well as medical institutions focusing on parasitic diseases, participated in this subnational assessment process. They were evaluated across several key areas, including theoretical knowledge, smear sample examination, and microscopic identification, with a specific focus on Plasmodium species and parasite eggs.ResultA total of 54 county-level representatives participated in this study, with 23 from 41 CDCs and 31 from medical institutes. Significant differences were observed in theoretical knowledge scores across various parasitic species (χ2 = 81.563, p < 0.001), with Plasmodium spp. achieving the highest score at 82.22%, while other species scored the lowest at 53.31%. The average scores for malaria blood films and modified Kato–Katz smears were reported as 6.39 ± 2.35 and 9.13 ± 1.54, respectively. The radar chart revealed that blood film staining had the lowest scoring rate at 41.96%, while extruded film achieved the highest at 86.16%. Significant differences were also found among different Plasmodium species (χ2 = 35.161; p < 0.001), with Plasmodium ovale recording the lowest score of 0.00%. The eggs of roundworm had the highest positive detection rate at 82.61%, whereas the eggs of Schistosoma japonicum had the lowest at 5.89%. Furthermore, women outperformed men in total scores, smears, and microscopic examinations (p < 0.05), while results indicated higher performance in eastern regions compared to western ones (p = 0.039). According to their overall scores, 14.8% of participants achieved certification at Level 1, while 51.9% attained Level 2.ConclusionThese findings underscore an ongoing necessity to bolster both theoretical understanding and skill proficiencies related to parasitic diseases—particularly in malaria blood smear analysis, detection of Plasmodium ovale, and identification of Schistosoma japonicum eggs, especially among men and western Hainan’s practitioner community.